Growth drivers in emerging capitalist economies before and after the Global Financial Crisis - Benjamin Jungmann (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper contributes to the ongoing growth models (GMs) debate by investigating the growth drivers of emerging capitalist economies (ECEs) in the periods before (2000-2008) and after (2009-2019) the Global Financial Crisis (GFC). By drawing mostly on post-Keynesian economics, six growth drivers are considered: Finance, i.e., household debt; changes in income distribution; price and non-price competitiveness, as well as commodity prices; and finally, fiscal policy. By conducting crosscountry simple and multiple linear regressions to explain the growth of 19 ECEs in both periods, we find that post-GFC growth was driven by non-price factors while price competitiveness played a role in neither period. Likewise, commodity prices did not drive growth either. In terms of distribution, our results indicate that cross-country growth was driven by rising income inequality in both periods; however, this relation lacks significance. In the post-crisis period, growth was associated with rising profit shares. While this relation also lacks significance, it has to be assessed against various possibilities for seemingly profit-led growth. Finally, with household debt accelerating and fiscal policy becoming more expansionary after the crisis, our results indicate a potentially more prominent role for these factors in driving post-crisis growth, however, this finding lacks robustness. We argue that the sparse robust findings result from ECEs' heterogeneity, particularly in terms of their growth models and subordinated financialization.
Keywords: E11; E12; E65; F62; F65; 330; growth model; growth driver; financialization; emerging capitalist economies; post-Keynesian economics